2015
DOI: 10.4103/0253-7613.153440
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive pills induced hemichorea in an adolescent female with polycystic ovarian disease

Abstract: Chorea is a neurological adverse effect of oral contraceptive pills (OCPs). The onset of chorea following OCPs usage varies widely from few weeks to several years. We report a rare case of chorea which developed within a week of starting OCPs in an adolescent girl with polycystic ovarian disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The underlying cause of chorea gravidarum appears to be increased levels of estrogen; patients who experience abnormal movements during pregnancy are at increased risk of hemichorea in association with oral estrogen, whether from oral contraceptive pills containing estrogen or from post-menopausal hormone replacement therapy [ 105 106 107 108 ] Studies have shown that estrogen increases dopamine release in the brain through several different mechanisms as well as by increasing dopamine receptor density post-synaptically [ 104 ]. The mechanism for estrogen-induced hemichorea, whether through pregnancy or oral administration, thus appears to be on the basis of pre-existing sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying cause of chorea gravidarum appears to be increased levels of estrogen; patients who experience abnormal movements during pregnancy are at increased risk of hemichorea in association with oral estrogen, whether from oral contraceptive pills containing estrogen or from post-menopausal hormone replacement therapy [ 105 106 107 108 ] Studies have shown that estrogen increases dopamine release in the brain through several different mechanisms as well as by increasing dopamine receptor density post-synaptically [ 104 ]. The mechanism for estrogen-induced hemichorea, whether through pregnancy or oral administration, thus appears to be on the basis of pre-existing sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple other medications have been identified as causing an asymmetric or hemichorea including gabapentin [ 113 ], valproate [ 114 ], amphetamine [ 115 ], anti-histamine [ 116 117 ], selective serotonin reuptake inhibitors [ 118 ], neuroleptics [ 119 ] and z-drugs [ 120 ]. As previously mentioned, oral estrogen has been associated with drug-induced chorea as well, although this appears to be through a specific hormonal mechanism [ 105 106 107 108 109 ]. Medication-induced chorea appears to be a heterogeneous group of conditions, likely with multiple mechanisms of action.…”
Section: Resultsmentioning
confidence: 99%
“…Although better reported in adults, anticholinergics, L-DOPA, dopamine-agonists, opioids, TCAs, baclofen and lithium may also cause chorea [ 16 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 ]. Oral contraceptives may cause chorea in adolescent girls, especially in patients with previous SC [ 183 , 184 ]. Myoclonus may be induced by opioids, SSRIs, etomidate, carbamazepine and its derivatives, ketamine and analgesic withdrawal [ 3 , 178 , 185 , 186 , 187 , 188 ].…”
Section: Drug-induced and Toxic Movement Disordersmentioning
confidence: 99%
“…[57,58]. Six cases of chorea were reported related to the use of oral contraceptive estrogen pills, which improved within weeks to months of hormone cessation [59,60]. The pathophysiology of chorea gravidarum is likely similar, if not identical to that of chorea secondary to estrogen supplementation; both conditions resolve as estrogen levels normalize.…”
Section: Metabolic and Pregnancy-related Choreamentioning
confidence: 99%